PUSKESMAS STELSEL BERDINDING BOTOL: SOLUSI INOVATIF MENINGKATKAN AKSES PELAYANAN KESEHATAN DI DAERAH ENDEMIK MALARIA - Savitri, Ariyani Novita; Purnamasari, Dwi Rizki; Alfiani, Fuzna; Ikrima, Iftita Rakhma; Octaviani, Lulu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Some areas of Indonesia are malaria endemic areas with the National Annual Parasite Incidence (API) is 2.4%. Inequality in the number of puskesmas is one of the causes of high rates of malaria transmission. Solution of this problem is to build new puskesmas in that areas. The costs of this construction can be reduced by utilizing waste plastic bottles to replace a brick as the wall of puskesmas. Next, the bottle walled puskesmas will be built in stelsel system in order to improve access to health services in malaria endemic areas. Thus, the rate of malaria transmission can be suppressed.